2006
DOI: 10.1515/bc.2006.018
|View full text |Cite
|
Sign up to set email alerts
|

The kinin system mediates hyperalgesia through the inducible bradykinin B1 receptor subtype: evidence in various experimental animal models of type 1 and type 2 diabetic neuropathy

Abstract: Both insulin-dependent (type 1) and insulin-independent (type 2) diabetes are complex disorders characterized by symptomatic glucose intolerance due to either defective insulin secretion, insulin action or both. Unchecked hyperglycemia leads to a series of complications among which is painful diabetic neuropathy, for which the kinin system has been implicated. Here, we review and compare the profile of several experimental models of type 1 and 2 diabetes (chemically induced versus gene-prone) and the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 115 publications
(109 reference statements)
2
18
0
Order By: Relevance
“…Thus far, the effect of KKS on the neuropathy induced by long-lasting diabetes has been focused on the suppressive effect of B1R on diabetic hyperalgesia (47). However, another important aspect of diabetic neuropathy is the hypoalgesia caused by polyneuropathy in peripheral nerves, which can lead to lower limb amputations that have a major impact on the quality of life and disability of diabetic patients (48).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the effect of KKS on the neuropathy induced by long-lasting diabetes has been focused on the suppressive effect of B1R on diabetic hyperalgesia (47). However, another important aspect of diabetic neuropathy is the hypoalgesia caused by polyneuropathy in peripheral nerves, which can lead to lower limb amputations that have a major impact on the quality of life and disability of diabetic patients (48).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of pain in the setting of diabetes is complex. Previous studies have implicated involvement alterations in the peripheral kinin system (Gabra et al, 2006) and in peripheral vanilloid receptors (Hong and Wiley, 2005), in addition to described spinal and supraspinal mechanisms (Calcutt, 2002;Ramos et al, 2007) in the development of pain. The first study of sodium channels in peripheral nerve in PDN identified increases in RNA and protein of several voltage-gated sodium channel ␣ subunit isoforms, although in that study the investigators did not observe an increase in Na V 1.7 RNA or protein (Craner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Pesquero et al [24] first described hypoalgesia in B 1 receptor-deficient mice. Gabra et al [25][26][27] suggest that the kinin system mediates hyperalgesia through the inducible BK B 1 receptor subtype in animal models of diabetic neuropathy. Diabetic hyperalgesia was absent after STZ administration in the model of type 1 diabetes in B 1 receptor knockout mice [25,28] .…”
Section: Discussionmentioning
confidence: 99%